Hypothyroidism and the risk of coronary artery disease in Saudi patients - Moeber M Mahzari; Abduallah H Alserehi; Saleh A Almutairi; Khaled H Alanazi; Mohammed A Alharbi; Mohamud Mohamud (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Hypothyroidism has been described in the literature as a risk factor for coronary artery disease (CAD). An association between thyroid-stimulating hormone (TSH) levels and CAD has been confirmed. In Saudi Arabia, there has been no study on the relationship between hypothyroidism and CAD. Therefore, the aim of this study was to investigate the prevalence and risk factors of CAD in patients with hypothyroidism. MATERIALS AND METHODS: This cross-sectional study conducted at King Abdulaziz Medical City in Riyadh (KAMC-R), included 412 adult hypothyroid patients who were followed up between 2013 and 2018. The data was collected on demographics, CAD-related risk factors, and hypothyroidism. In addition, relevant laboratory tests, including thyroid function tests, lipid profile, and hemoglobin A1c, were collected. SPSS version 28.0 was used for data analysis. Categorical data were presented as frequencies and percentages, while mean and standard deviations were computed for the numerical data. Student's t-test used to test statistical significance for numerical variables and Chi-square test was performed to test the differences between categorical variables. Multivariate binary logistic regression was used to determine the effects of gender, BMI, family history (CAD), smoking, hypertension, and TSH on CAD. RESULTS: Of the 412 hypothyroid patients, 21.8% were diagnosed with CAD, with more prevalence in men (44.15%) than in women (15.4%). About 46% had hypertension, 2.2% were smokers, and 2.4% had family history of CAD. Older age was significantly associated with a higher prevalence of CAD compared to younger age groups. The mean of TSH was significantly higher in CAD patients than non-CAD patients before and at diagnosis with CAD (P < 0.001). For every 1mIU/L increase in the TSH level, the odds of developing CAD increased significantly by 4.8% (P = 0.014). The odds ratios for other CAD risk factors were 3.13 for males, 8.1 for smoking, 2.48 for hypertension, and 9.9 for family history of CAD (P < 0.05). CONCLUSION: The prevalence of CAD in hypothyroid patients was higher than in the general population. TSH level was significantly associated with CAD. Male gender, older age, smoking, hypertension, family history of CAD, and high TSH level increased the likelihood of developing CAD.